Identification of Enhancing Factors for Increasing The Power Competitiveness of Small Medium Industry of Batik in Sidoarjo District With Integration of Green Innovation Approach and ISM - Ida Kusnawati Tjahjani; Abdul Hakim; Bagyo Yanuwiadi; Dias Satria (LPPM of NAROTAMA UNIVERSITY, 2020)
This research was conducted at the Small and Medium Industry (IKM) of batik in the district of Sidoarjo, which is one of 15 districts in East Java who chose One Village One Product (OVOP) as strategies increase the power of competitiveness. There are many problems with SME batik ranging from resources, production processes to product sales, which affect the chosen competitiveness strategy. The respondents were entrepreneurs, the office of SMEs, the Ministry of Industry and Trade, the sub-district, and the village. This research aims to identify the inhibiting factors of increasing competitiveness in the small and medium batik industry in the district of Sidoarjo. The data collection process uses a questionnaire compiled with the Green Innovation approach with five main variables, Green Resource, Green Process, Green Product, Green Innovation, and Competitive Advantage. Green Innovation is a process of continuous innovation that considers the integration of the environment, finance, social systems in the company from the stage of ideas through research and development and commercialization that affect new products, services, technology, business, and organizational models. Determination of alternatives and strategy analysis using the Interpretative Structural Modeling (ISM) approach is a method that uses the opinions of experts on the questionnaire that has been distributed. Based on the analysis results, 14 inhibiting factors and six priority levels were obtained, with the highest value of the power driver in the training and outreach factor (10) as the main inhibiting factor in increasing competitiveness. Therefore, it requires the involvement of all parties related to the batik SMEs to improve their competitiveness and the strategies they choose.